A literature review on the causal relationship between Occlusal Factors (OF) and Temporomandibular Disorders (TMD) VI: final conclusions - Acosta-Ortíz, Rodolfo (Revista Facultad de Odontología Universidad de Antioquia, 2011)
Introduction: this is the sixth and last article of this extensive and complete literature review whose purpose was to evaluate the possible causal relationship between occlusal factors (OFs) and temporomandibular disorders (TMDs). Methods: the analysis included only the analytical epidemiologic studies —out of all the articles found —, and they were analyzed using the epidemiologic criteria commonly used to establish causality (cause/effect). Results: the findings suggest that, although the first criterion —strength of the associations between OFs and TMDs— existed, other criteria such as consistency with other studies, temporal sequence of events, dose-response relationship and biologic plausibility cannot be supported with the currently available scientific information. Therefore, if there is a causal relationship, it is a weak one. Conclusion: the scientific information available today provides weak and confusing evidence regarding the causal relationship between OFs and TMDs. More and better studies are needed, with improved research method that allow controlling confounding variables. This will pave the way for clearer and more concrete results that will also help to make more solid interpretations and conclusions about the possible causal relationship between OFs and TMDs.